Hubungan Motivasi dan Hasil Belajar Terhadap Pembelajaran Matematika di Sekolah Dasar 02 Taeh Bukik - Lena, Mai Sri; Puspita Sari, Indah dwi; Dayanur, Ilhami; Azizah, Kisma Umi; Sari, Melia Indra (Wahana Sekolah Dasar, 2021)
The aim of this research was to find out the significant relationship between learning motivation and learning outcomes in mathematics learning. This study consists of two variables, namely variable X and variable Y. In this study variable X is learning motivation and variable Y is learning outcomes. The type of research used in research is quantitative. The research method used in this study was the correlation study and the population in this study is the fourth-grade students of SDN 02 Taeh Bukik and the sample used in this study was 12th-grade students. The sampling technique used in this study was probability sampling, namely simple random sampling. Data collection techniques used in this study were tests and questionnaires. Data analysis techniques used by researchers to analyze data or determine the assessment of the relationship of motivation variables with student learning outcomes in mathematics using correlation was the product-moment. The result of this study indicated that there was a significant relationship between motivation and learning outcomes on students' mathematics learning at grade IV SDN O2 Taeh Bukit.